Proof of the Legal Power of Electronic Certificates Against Criminal Acts of Forgery - Zulki Zulkifli Noor (Journal of Law, Politic and Humanities, 2024)
his study aims to analyze the legal force of electronic certificates in relation to the crime of forgery. Electronic certificates as one of the digital legal instruments are recognized in Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), providing a strong legal basis for their recognition and validity in the evidence process. However, in its application, there are various challenges, especially related to data security and the risk of forgery. Through a normative legal approach, this study examines various laws and regulations as well as relevant case studies to evaluate how electronic certificates can be used as valid evidence in court. The results of the study show that although electronic certificates have legal force, there are still gaps in regulation and implementation that can be exploited by criminals to commit forgery. Therefore, increased regulation and supervision are needed to ensure the reliability of electronic certificates in the legal process.